Improving the extraction of Ara h 6 (a peanut allergen) from a chocolate-based matrix for immunosensing detection: Influence of time, temperature and additives - Alves, Rita C. (2019)
The extraction of Ara h 6 (a peanut allergen) from a complex chocolate-based food matrix was optimized by testing different temperatures, extraction times, and the influence of additives (NaCl and skimmed milk powder) in a total of 36 different conditions. Analyses were carried out using an electrochemical immunosensor. Three conditions were selected since they allowed the extraction of the highest levels of Ara h 6. These extractions were performed using 2g of sample and 20ml of Tris-HNO3 (pH=8) containing: a) 0.1M NaCl and 2g of skimmed milk powder at 21°C for 60min; b) 1M NaCl and 1g of skimmed milk powder at 21°C for 60min; and c) 2g of skimmed milk powder at 60°C for 60min. Recoveries were similar or higher than 94.7%. This work highlights the importance to adjust extraction procedures regarding the target analyte and food matrix components.